Evaluation of an occupational competency-based curriculum and its impacts on learning outcomes - Wei, Ching-Fang; Lii , Peirchyi (Technium Social Sciences Journal, 2022)
This study explores the expectations of enterprise recruiters regarding job seekers in terms of required competencies and how higher education should contribute to preparing students for future employment. This study employs an occupational competency-based pedagogical model. Based on in-depth interviews with ten senior workers in the aviation and education industries, a four-year longitudinal qualitative research was conducted. After the conclusion of the training program, data on the employment status of research participants were collected. Further, a holistic interpretation and validation was provided for the competency-based pedagogical model. The results demonstrate that students developed stronger learning motivation and better employability because of a competency-based curriculum and training.